20. Whiteboard Products - Cox, Nolan; Hoyme, Cindy; Martindale, Neil; Morch, Liz (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
A common feature of online collaborative methodologies is the whiteboard, a tabula rasa type area in which participants can share simultaneous applications and learning experiences. The current report is the first in this series to examine a range of whiteboard technologies specifically. Some are available in stand-alone freeware products such as Groupboard, while others are components of license-based packages such as VClass and WebCT. The whiteboard features of these three products are reviewed.